The influence of store atmosphere, visual merchandising and service quality on consumer satisfaction (study at cafe aola Paciran) - Faiz, Eka; Inggrit, Levia; Ayu Novitasari, Diah; Nur Azizah, Luluk; Anggraini Widyastutik, Yunita (Proceeding of International Management Conference and Progressive Papers, 2023)
The purpose of the study is to determine the influence of variables from store atmosphere, visual merchandising, service quality on consumer satisfaction. Study at Cafe Aola Paciran. Using quantitative methods. 69,315. The sample size was 100 respondents. The analysis method is Multiple Linear regression. Hypothesis Testing through Statistical Tests Namely t Test and F Test. Based on the research it can be concluded that the variables Store Atmosphere, Visual Merchandising and Quality of Service against Quality of Service at Cafe Aola Paciran